Possible relationship between the gut leaky syndrome and musculoskeletal injuries: the important role of gut microbiota as indirect modulator - Jesús Álvarez-Herms; Adriana González; Francisco Corbi; Iñaki Odriozola; Adrian Odriozola (AIMS Press, 2023)
This article aims to examine the evidence on the relationship between gut microbiota (GM), leaky gut syndrome and musculoskeletal injuries. Musculoskeletal injuries can significantly impair athletic performance, overall health, and quality of life. Emerging evidence suggests that the state of the gut microbiota and the functional intestinal permeability may contribute to injury recovery. Since 2007, a growing field of research has supported the idea that GM exerts an essential role maintaining intestinal homeostasis and organic and systemic health. Leaky gut syndrome is an acquired condition where the intestinal permeability is impaired, and different bacteria and/or toxins enter in the bloodstream, thereby promoting systemic endotoxemia and chronic low-grade inflammation. This systemic condition could indirectly contribute to increased local musculoskeletal inflammation and chronificate injuries and pain, thereby reducing recovery-time and limiting sport performance. Different strategies, including a healthy diet and the intake of pre/probiotics, may contribute to improving and/or restoring gut health, thereby modulating both systemically as local inflammation and pain. Here, we sought to identify critical factors and potential strategies that could positively improve gut microbiota and intestinal health, and reduce the risk of musculoskeletal injuries and its recovery-time and pain. In conclusion, recent evidences indicate that improving gut health has indirect consequences on the musculoskeletal tissue homeostasis and recovery through the direct modulation of systemic inflammation, the immune response and the nociceptive pain.